Nudge the judge? Theorizing the interaction between heuristics, sentencing guidelines and sentence clustering - Marder, Ian D.; Pina-Sánchez, Jose (Criminology & Criminal Justice, 2020)
Although it has long been acknowledged that heuristics influence judicial decision making, researchers have yet to explore how sentencing guidelines might interact with heuristics to shape sentencing decisions. This article contributes to addressing this gap in the literature in three ways: first, by considering how heuristics might help produce the phenomenon of sentence clustering, in which a significant proportion of sentences are concentrated around a small number of outcomes; second, by reflecting on the role of sentencing guidelines as a feature of the environment within which sentencing decisions are made; and third, by analysing the guidelines from Minnesota and from England and Wales, theorizing how their content might interact with heuristics to make clustering more or less likely. Ultimately, we argue that sentencing guidelines likely affect the role played by heuristics in shaping sentencing decisions and, consequently, that their design should be informed by research evidence from the decision sciences.